Methods of quality control signals in digital radio relay and tropospheric communication station (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
Introduction. The modern digital communication systems such as radiorelay and tropospheric communication, their advantages before the analogue systems, requirements for digital systems in terms of accurate data transmission and control errors in service monitoring are described. Performance error in digital path. The overview of main error indicators in digital communication systems, approved by international telecommunication union is provided in this section. It contains a brief description of determine the readiness state and error seconds calculation method. Methods for evaluating the quality of digital signal. The questions measuring key indicators of errors that can occur in the digital channel, such as BER - (Bit Error Ratio) and ES -(Error Seconds) are considered. The description of the methods for measuring these indica-tors, so as out of service and in service monitoring is given. The errors detection method used the E1 stream structure and their efficiency is described. The diagnostic methods in the digital path in service monitoring and applications features for authentic definition of the bit errors coefficient based on CRC-4 procedure are compared. One of the methods offers to get probabilistic relations between the parameters based on BER and ES / SES for the evaluation digital path use, using a probabilistic model of the processes occurring in the measurements. Mask of bit errors ratio of the relative measurements time is produced. Conclusions. The methods of control quality signals for errors in digital communication systems compared different approaches for indicating and calculation the main indicators of errors, such as BER and ES/SES are analyzed. It is recommended to use CRC-4 procedure with probabilistic model of the processes occurring in the measurements using distribution mask bit error probability for channels with different bandwidth for the quantitative evaluation the quality radio path.